Cost-comparison of third generation transcatheter aortic valve implantation (TAVI) devices in the German Health Care System. (1st March 2019) - Veulemans, Verena; Piayda, Kerstin; Afzal, Shazia; Polzin, Amin; Quast, Christine; Jung, Christian; Westenfeld, Ralf; Zeus, Tobias; Kelm, Malte; Hellhammer, Katharina
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has a substantial impact on daily cardiovascular care delivery based on issues such as cost effectiveness and economic value within a restricted health care budget. Until now, potential financial benefits of third generation valve models have not been evaluated in a real-world setting. Methods and results: We identified 204 eligible patients (Jan 2014-Sep 2016) who either received the balloon-expandable Edwards Sapien 3 (ES3) or the self-expandable Medtronic Evolut R (MER). Baseline information, procedural characteristics, 30-day outcome as well as in-hospital costs and reimbursement were collected and analyzed. The major cost driver was initial valve-kit costs with a significantly higher amount in the ES3 group, which was set at 0 with the lower price (ES3/MER: +4390.0€ ± 3.807.0 vs. 0.0€ ± 734.1; p < 0.01). However, initial valve-kit costs were balanced by additional material costs in the MER cohort. Overall costs did not differ significantly between valve models (ES3/MER: x + 13.808.0€ ± 5.595.0 vs. x + 10.681.0€ ± 4.518.0; p = 0.6885) and reimbursement was moderate (ES3/MER: 1.649.7€ vs. 4776.7€). Conclusion: Quality, success rate, and costs were comparable between third generation devices. Initial valve-kit costs were significantly higher in the ES3 group, whereas overall costs did not significantly differ between the two valve types. Highlights: A major cost driver during TAVI with third generation devices is material expenditure. Overall costs do not differ significantly between valve models. Overall reimbursement is moderate for this complex procedure. Potential cost saving strategies will be mandatory in the future.